International Women's Day in China: Feminism Meets Militarised Nationalism and Competing Political Party Programs. Issue 1 (2nd January 2016) - Edwards, Louise
Abstract: This article examines the contested history of International Women's Day (IWD) in China during the first half of the twentieth century. It explores the processes of cooption and subsumption that have diminished the "international" in IWD in the Chinese context as the feminist movement confronted powerful forces of nation building, party building and militarised warfare as battles waged between Japan and China, and between the Chinese Communist Party and the Nationalist Party. It argues that IWD was put to use by myriad competing groups and these appropriations diminished the event's original goal of forging international solidarity among women around the world.